Prevalence of Rheumatic Heart Disease in a Public School of Belo Horizonte - Miranda,Lavinia Pimentel (2014)
Background: Previous studies indicate that compared with physical examination, Doppler echocardiography identifies a larger number of cases of rheumatic heart disease in apparently healthy individuals. Objectives: To determine the prevalence of rheumatic heart disease among students in a public school of Belo Horizonte by clinical evaluation and Doppler echocardiography. Methods: This was a cross-sectional study conducted with 267 randomly selected school students aged between 6 and 16 years. students underwent anamnesis and physical examination with the purpose of establishing criteria for the diagnosis of rheumatic fever. They were all subjected to Doppler echocardiography using a portable machine. Those who exhibited nonphysiological mitral regurgitation (MR) and/or aortic regurgitation (AR) were referred to the Doppler echocardiography laboratory of the Hospital das Clínicas of the Universidade Federal of Minas Gerais (HC-UFMG) to undergo a second Doppler echocardiography examination. According to the findings, the cases of rheumatic heart disease were classified as definitive, probable, or possible. Results: Of the 267 students, 1 (0.37%) had a clinical history compatible with the diagnosis of acute rheumatic fever (ARF) and portable Doppler echocardiography indicated nonphysiological MR and/or AR in 25 (9.4%). Of these, 16 (6%) underwent Doppler echocardiography at HC-UFMG. The results showed definitive rheumatic heart disease in 1 student, probable rheumatic heart disease in 3 students, and possible rheumatic heart disease in 1 student. Conclusion: In the population under study, the prevalence of cases compatible with rheumatic involvement was 5 times higher on Doppler echocardiography (18.7/1000; 95% CI 6.9/1000-41.0/1000) than on clinical evaluation (3.7/1000-95% CI).